Tinjauan Hukum Pembebasan Lahan untuk Kepentingan Umum dalam Perspektif Hukum Perdata - Novita Komalasari; Mastorat; Gufran (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This research examines the legal mechanism of land acquisition for public interest in the perspective of civil law through a normative research approach. By analyzing various relevant laws and regulations including Law No. 2/2012, Law No. 20/1961, and UUPA (Law No. 5/1960), this research finds several crucial findings. First, there is regulatory dualism that creates legal uncertainty in the implementation of land acquisition, especially regarding the mechanism of revocation of rights and determination of compensation. Second, the protection of landowners' rights is not yet fully in accordance with the principles of civil law that uphold individual property rights. Third, various conflicts often arise due to unclear public interest criteria and differences in interpretation of land value. This study concludes that harmonization of regulations, affirmation of a more operational definition of public interest, and strengthening of individual rights protection mechanisms are needed to create a more fair and equitable land acquisition process. The findings are expected to serve as input for the improvement of land acquisition regulations and practices in Indonesia.